Vitamin D status and the immune assessment in 22q11.2 deletion syndrome. (16th April 2020) - Legitimo, A.; Bertini, V.; Costagliola, G.; Baroncelli, G. I.; Morganti, R.; Valetto, A.; Consolini, R.
Summary: 22q11.2 deletion syndrome (22q11.2DS) is characterized by a heterogeneous phenotype, including alterations in phospho‐calcium metabolism and immunodeficiency. We analyzed vitamin D status and the immune assessment, focusing on T cell subpopulations and dendritic cells (DCs) in a cohort of 17 pediatric 22q11.2DS patients and 17 age‐matched healthy subjects. As antigen‐presenting cells, DCs are the main target of vitamin D, promoting a tolerogenic T cell response. Patients were subdivided into three groups according to the parameters of phospho‐calcium metabolism and serum levels of 25OHD: normal values, vitamin D deficiency and hypoparathyroidism. Different degrees of T cell deficiency, ranging from normal to partial T cell numbers, were observed in the cohort of patients. The group with vitamin D deficiency showed a significant reduction of naive T cells and a significant increase of central memory T cells compared to controls. In this group the number of circulating DCs was significantly reduced. DC decrease affected both myeloid and plasmacytoid DC subsets (mDCs and pDCs), with the most relevant reduction involving pDCs. A direct correlation between 25OHD levels and recent thymic emigrant (RTE) and DC number was identified. Despite the limited cohort analyzed, our results show that deficiency of the pDC subset in patients with 22q11.2DS may be included among the causative factors of the progressive increase of risk of autoimmune diseases in these patients. As most patients suffer from increased susceptibility to infections and heightened prevalence of autoimmune disorders, we suggest a potential role of vitamin D supplementation in preventing autoimmune or proinflammatory diseases in 22q11.2DS. Abstract : This study analyzes vitamin D status and the immune assessment in patients with 22q11.2 deletion syndrome (22q11.2DS), with the main focus on dendritic cells (DCs). Patients with vitamin D deficiency show a significant reduction of DCs number, with the most relevant decrease observed in plasmacytoid DCs (pDCs). As most patients suffer from increased susceptibility to infections and heightened prevalence of autoimmune disorders, we suggest that the pDC defect could be contributing to the progressive risk of autoimmune diseases in patients with 22q11.2DS. A potential role of vitamin D supplementation in preventing autoimmune or pro‐inflammatory diseases in these patients is discussed.